2020
DOI: 10.1371/journal.pone.0227637
|View full text |Cite|
|
Sign up to set email alerts
|

Hesperidin improves insulin resistance via down-regulation of inflammatory responses: Biochemical analysis and in silico validation

Abstract: Leptin resistance and co-existing insulin resistance is considered as hallmark of dietinduced obesity. Here, we investigated therapeutic potential of hesperidin to improve leptin and insulin resistance using high fat diet (HFD)-induced obese experimental animal model. We also performed in silico studies to validate therapeutic effectiveness of hesperidin by performing protein-ligand docking and molecular dynamics simulation studies. Group 1 was identified as control group receiving vehicle only. Group 2 was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Akiyama and collaborators also reported a recovery of adiponectin levels mediated by hesperidin both in T1D and T2D models [36,44]. In addition to the effects observed in diabetic models, improvement of glucose metabolism and insulin resistance were also described by our group and others in other animal models of human diseases that are associated with alterations in glucose metabolism, such as metabolic syndrome (MetS) and obesity [47][48][49][50][51].…”
Section: Effects Of Hesperidin On Glucose Homeostasismentioning
confidence: 66%
See 1 more Smart Citation
“…Akiyama and collaborators also reported a recovery of adiponectin levels mediated by hesperidin both in T1D and T2D models [36,44]. In addition to the effects observed in diabetic models, improvement of glucose metabolism and insulin resistance were also described by our group and others in other animal models of human diseases that are associated with alterations in glucose metabolism, such as metabolic syndrome (MetS) and obesity [47][48][49][50][51].…”
Section: Effects Of Hesperidin On Glucose Homeostasismentioning
confidence: 66%
“…In this sense, there are several studies demonstrating that hesperidin exerts beneficial effects on lipid accumulation and adiposity [71,72,77,78]. In animal models of obesity or MetS, a body-weight-reducing effect has been widely reported in response to hesperidin treatment [47][48][49][50][51], as well as a reduction in adipose tissue weight [25,48,50,51]. In contrast, Mosqueda-Solis et al reported no significant changes in body weight after a daily hesperidin administration (100 mg/kg body weight) for eight weeks in Western-diet-fed rats, although hesperidin treatment resulted in a decreased size of adipocytes [78].…”
Section: Effects Of Hesperidin On Lipid Profile and Adipositymentioning
confidence: 99%
“…For instance, hesperidin upregulated the GLUT2, GLUT4, IRS1 and glucokinase levels and downregulated the hepatic fatty acid oxidation and carnitine palmitoyl transferase activity in type-2 diabetes to improve hyperlipidaemia and hyperglycaemia [ 34 , 35 ]. Kanwal et al also reported that hesperidin relieved insulin resistance by inhibiting inflammatory responses [ 36 ]. In this study, our study showed that HG treatment successfully exhibited a low antioxidant activity, and accompanied by mitochondrial dysfunction and insulin resistance in LO2 cells, suggesting that the diabetic model of oxidative stress was successfully established in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 15 years of type 1 diabetes (T1D) research, in-silico clinical trials (ISCTs), performed using simulators relying on mathematical models of glucose-insulin system dynamics, have accelerated the development of new treatments 1 - 4 and drugs, 5 - 7 and have facilitated the design of clinical studies. 8 - 11 ISCTs allow investigators to carry out a vast number of experiments quickly, in order to evaluate, for example, new algorithms in high-risk scenarios, and so offer considerable economic and human resource savings.…”
Section: Introductionmentioning
confidence: 99%